ہندوستان میں برطانوی دور اقتدار میں مسلم متکلمین کی مشنریز سے مزاحمت: Muslim Theologians Resistance to Missionaries During the British Rule in India (Al-Qamar, 2023)
Evidence of the existence of Christianity in India can be found from the second century AD. When the industrial revolution came in European countries, European countries established colonies in other countries of the world and in this context, many European countries turned to India,but Britain was successful in them. The British government through the East India Company like When he started gaining power, he made a plan to convert the people of India into Christianity. For this purpose, priests from European countries were called to preach Christianity to the Muslims here. The religious literature of India was made suspicious and various missionary organizations were given full support by the government to force the Indian people to accept Christianity through threats or greed. All the doubts raised by him were countered in the form of books and debates, so in this article the life conditions and services of these scholars will be presented.
Keywords: Missionaries; Muslim Theologians; Resistance; British Rule; India